Assessing the Willingness to Elaborate among Young Students: Psychometric Evaluation of a Swedish Need for Cognition Scale - Stenlund, Tova; Jonsson, Bert (Frontiers in Education, 2017)
The personality trait Need for Cognition (NFC) has been studied for many years, and found to be important for individuals’ educational achievement. The original NFC-scale was developed in the eighties, and during the following decade the scale was translated and adapted into a number of other languages. A renewed interest for the personality trait of NFC has made these scales interesting to use. It is though vital that instruments used for studies of individual differences in the area of educational research, or in any other area, can portray valid results today. The aim of the present paper was to evaluate validity and reliability of the short version of the Mental Effort Tolerance Questionnaire, a Swedish adaption of the NFC-scale made in 1991, which has not been previously evaluated. This study involved 420 young students, and the evaluation of reliability includes a study of temporal stability (test-retest), as well as internal stability. Further, the evaluation of validity includes construct and criterion validity. Regarding reliability, the results showed a test-retest reliability coefficient of .88 (n = 108), and an internal stability (Cronbach’s alpha) of .88 (n = 420). Evaluation of construct validity found evidence for a five factor dimensional structure (n = 420), discriminant validity to measures of general intelligence (r = .25; n = 122), working memory (r = .22; n =164), and the personality trait Grit (r = .26; n = 169). Finally, criterion validity was found for grades (r =.35; n =125). Overall, the results of the evaluation show that the inferences made from the results of the short version of the Swedish NFC-scale exhibits satisfactory reliability and validity, suggesting that the questionnaire can be used in educational contexts. The questionnaire might, however, benefit from being even more shortened.